Warum kriegt Europa die Eurokrise nicht in den Griff? - Adalbert Winkler (Wirtschaftsdienst, 2012)
Die Beschlüsse des Euro-Gipfels vom Juni 2012 haben bei deutschen Ökonomen heftige Kritik ausgelöst. Der Autor fragt, welche Konsequenzen es gehabt hätte, wenn die Ratschläge der Ökonomen schon in der Finanzkrise 2008 befolgt worden wären, und befürchtet, dass der Verzicht auf eine am Beispiel des Jahres 2008 orientierte Krisenbekämpfungsstrategie einen Teufelskreis auslöst, der zum Sprengsatz für die Währungsunion werden kann. – – This paper argues that Europe is unable to get the euro crisis under control because it has chosen a crisis management strategy that is diametrically opposed to the one applied in the global financial crisis. In 2008, crisis management focused on measures that instilled confidence, while policies solving more fundamental problems were only applied at a later stage. In the euro crisis - following the advice of German economists strongly attached to the views of 'Ordnungspolitik' - crisis management aims at solving the fundamental problems first. Moreover, measures successfully applied in the 2008 crisis, including joint liability mechanisms, are now portrayed as counterproductive and even harmful. As a result, Europe has made little progress in fighting the crisis and creating the institutional foundations to do so successfully.
Keywords: E44; F34; F36; 330; Öffentliche Schulden; Haushaltsdefizit; Eurozone; Ordnungspolitik; Europäische Wirtschafts- und Währungsunion; EU-Staaten